Fluid Migration and Brittle Tectonothermal Evolution in the Central Fennoscandian Shield - Recorded by Fracture Minerals and Wall Rock Alteration - Sandström, Björn (2009)
The Forsmark area in central Sweden has been investigated as a potential geological host for a final repository of spent nuclear fuel by the Swedish Nuclear Fuel and Waste Management Company (SKB). High quality drill core material from the upper 1 km of the central Fennoscandian Shield has been obtained during the site investigations and has provided a unique opportunity for detailed fracture mineralogical investigations. In this thesis, a multi-analytical approach for recognising events of fluid migration and brittle tectonothermal evolution by analysis of fracture minerals and wall rock alteration is presented. The basis for this study has been the establishment of a relative sequence of fracture mineralisations obtained by investigations of cross-cutting relations and mineral overgrowths. Based on this sequence, representative fracture mineral samples have been selected for further analysis, e.g. 40Ar/39Ar dating, stable isotopes, trace element geochemistry and fluid inclusions. Statistical analysis of the orientation of fractures lined with different minerals has also been carried out. Four major events of fracture mineralisation have been distinguished in the Forsmark area. The two first events are associated with hydrothermal alteration of the wall rock, causing a red-staining due to hematite dissemination. The alteration is characterised by chloritisation of biotite, saussuritization of plagioclase and partial replacement of magnetite by hematite. The oldest event occurred sometime between 1.8 and 1.1 Ga, possibly during a late stage of the Svecokarelian orogeny. Precipitation of epidote, quartz and chlorite occurred at temperatures between c. 200° and 350°C in preferably sub-horizontal to gently dipping fractures or steep, WNW-ESE to NW-SE fractures. These fractures are cut by fractures sealed with hematite-stained adularia and albite, prehnite, hematite-stained laumontite, calcite and chlorite which are prominent along steep, ENE-WSW to NNE-SSW and NNW-SSE fractures. These minerals precipitated under ...